2022
DOI: 10.55329/fbhr3456
|View full text |Cite
|
Sign up to set email alerts
|

Interact or counteract? Behavioural observation of interactions between vulnerable road users and autonomous shuttles in Oslo, Norway

Abstract: The current paper presents the results of behavioural observations in a field experiment with automated shuttles in Oslo, Norway. Video observations were conducted at five fixed locations along a challenging 1.2 km automated shuttle line with varying traffic conditions. Observed interactions between vulnerable road users and automated shuttles were coded using a predefined codebook, which allowed a structured quantitative analysis. The paper identified several potentially risky types of situations in which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The main transport provider in the Oslo-region, Ruter, has completed several tests of SASs (Green et al, 2022). Research has found that several of these early tests violate traffic regulations and provoke evasive maneuvers from other road users (Ceunynck et al, 2022). These SASs have engendered dangerous situations with their slow and passive driving (Mirnig et al, 2022;Pokorny et al, 2021), and may be susceptible to be taken advantage of by other road users due to its' passive driving (Bjørnskau et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The main transport provider in the Oslo-region, Ruter, has completed several tests of SASs (Green et al, 2022). Research has found that several of these early tests violate traffic regulations and provoke evasive maneuvers from other road users (Ceunynck et al, 2022). These SASs have engendered dangerous situations with their slow and passive driving (Mirnig et al, 2022;Pokorny et al, 2021), and may be susceptible to be taken advantage of by other road users due to its' passive driving (Bjørnskau et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, trust may entail fears related to the social situation, data hacking, traffic safety, system performance and equipment failure, and other factors. Some recent pilots of SASs in Europe have found that the vehicles are too cautious while driving, creating concerns about SASs not being effective enough as a public transportation service and even detrimental to safety (Ceunynck et al, 2022;Pokorny et al, 2021). Thus, at present, SASs may not be technologically mature enough to claim a place in people's everyday transport (Mouratidis & Serrano, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several pilots have been conducted in the Norwegian context, and the public transportation authority in the Oslo region, Ruter, has recently been attempting to implement SASs as part of their transport system. These pilots have found that autonomous buses were often in conflict with traffic regulations, provoking evasive maneuvers from cyclists and pedestrians (Ceunynck et al, 2022). This may further deteriorate the public perception of SASs.…”
Section: Introductionmentioning
confidence: 99%